Prevalence of contraceptives and unmet need for family planning: does geographical location play a role? - Dutta, Palas; Debnath, Sumon Chandra; Alamin, Md; Roy, Ropak Chandra (Asian Journal of Medical and Biological Research, 2017)
Coastal women are the most socio-economically disadvantaged clusters with low literacy and deprived economic and living conditions. The study aims at measuring contraception and unmet need for contraceptive need among married women in the reproductive age group. A cross-sectional study was carried out among222 married women of in a coastal area of Bangladesh. The majority of the respondents (33.8%) were 31 years and above with mean (± SD) age at marriage was 16.2 ± 2.3 years. Most (85.6%) of the study sample were housewives and maximum (84.7%) were literate. About half (50.9%) of them belongs to the single family and about two-thirds (60.4%) monthly family income between 5000 and 10000 Taka. The mean age of women at marriage was 16.2± 2.2 SD, out of which, about two third (63.9%) experienced marriage below 18 years. The average number of pregnancies was 1.9 ± 1.0 SD, out of which, 39.6% experienced two pregnancies. The current contraceptive prevalence rate among married women was 80.2%. The prevalence of unmet need for family planning was 13.5%. The major reason for non-use of contraception among women with unmet need was the husbands opposition. Asian J. Med. Biol. Res. June 2017, 3(2): 175-181